EXPLORING FACTORS THAT CAUSE THE STUDENTS DEMOTIVATION IN LEARNING ENGLISH GRAMMAR AND ENGLISH WRITING STIBA IEC STUDENTS DURING COVID-19 PANDEMIC - Mettadewi, Bella; Sitohang, Mangangar; Sutrisno, Bejo (STIBA IEC JAKARTA, 2023)
This research aims to find out what are the demotivating factors experienced by STIBA IEC students while studying English grammar and English writing during a pandemic. In addition, researcher also finds out what are the main factors that make them demotivated and what suggestions do students want to convey so that online learning can take place well. A qualitative method is used in this research where the researcher interviewed 10 participants who came from semester 2 and semester 4 students from three different shift classes. As a result, there are 2 kinds of influencing factors, namely external factors and internal factors. External and internal factors are divided into several kinds. The implication of this is readers can find out what factors are experienced by students and can get solutions to existing problems.